Management of paroxysmal atrial flutter that occurred in an outpatient prior to dental surgery: a case report - Hajime Shimoda; Tetsu Takahashi (BMC, 2019)
Abstract Background It is essential to accomplish the appropriate emergency care particularly in patients undergoing stressful dento-oral surgical procedures. Atrial flutter may be induced by sympathetic hypertonia due to excessive mental and physical stress. There is no report regarding dental care in patients with atrial flutter. Herein, we describe a rare case of the antiarrhythmic management in an outpatient who presented with an electrocardiographic finding of paroxysmal atrial flutter before the initiation of the dento-oral surgical procedure. Case presentation A 60-year-old male patient was scheduled for a dental extraction. He had a history of angina pectoris, diabetes mellitus, and paroxysmal atrial fibrillation with medication. The preoperative electrocardiogram (ECG) revealed left ventricular hypertrophy and ST-T segment abnormality. Immediately before the dental extraction, II-lead ECG revealed atrial flutter; however, he complained of few subjective symptoms, such as precordial discomfort or palpitation. Observing the vital signs, ECG findings, and the general condition of the patient, low dose diltiazem was immediately administered by continuous infusion in order to control the heart rate and prevent atrial flutter-induced supraventricular tachyarrhythmia. Special attention was paid to prevent any critical cardiovascular condition under a preparation of intravenous disopyramide and verapamil and a defibrillator. The intravenous administration of diltiazem progressively restored the sinus rhythm after converting atrial flutter into atrial fibrillation, resulting in the prevention of tachycardia, and then was found to be appropriate as a prophylactic therapy of tachyarrhythmia. Conclusions The present case suggests that it is possible to successfully manage some of such patients using our method during dento-oral surgery which is likely to be associated with mental and physical stress. Therefore, it is essential to accomplish an initial emergency care in parallel to the differential diagnosis of unforeseen serious medical conditions or paroxysmal arrhythmia such as atrial flutter.